A dataset on bathymetry and hydrology of an emerging periglacial lagoon in Svalbard, ArcticMendeley Data - Andrius Šiaulys; Aleksej Šaškov; Greta Kilmonaitė; Dzmitry Lukashanets; Tobia Politi; Aurelija Samuilovienė; Anastasija Zaiko; Sergej Olenin (Data in Brief)
In recent decades, the melting of glaciers has led to a consistent increase in the number of periglacial coastal lagoons that form in the place of receding glaciers in Svalbard, European Arctic. There is limited data on the geomorphology and hydrology of these novel formations, primarily because conducting research in remote polar regions is logistically challenging and expensive.We present hydrological and bathymetric data collected in 2022-2024 in a newly formed lagoon located in the western part of Spitsbergen (Svalbard), between Eidembreen glacier and Eidembukta bay. The lagoon consists of several semi-isolated water bodies characterized by distinct bottom geomorphology and complex hydrological structure. The deepest part (42.8 m) was observed near the glacier front, while extensive shallow areas have depths of less than 1 m. Various hydrological parameters were measured during surveys (temperature, salinity, oxygen saturation, dissolved oxygen concentration, pH, photosynthetically active radiation, turbidity, conductivity, density, pressure and sound velocity), which indicate strong vertical stratification with pronounced halocline and thermocline in some parts of the lagoon.The data collected will be utilized to analyze the physical and geographical conditions of the lagoon, as well as the distinguishing characteristics of its various sections, which vary in age by several decades. The data is essential for understanding the distribution patterns of biodiversity and the functioning of the lagoon ecosystem, which is the subject of a separate study. Furthermore, this data can be utilized to monitor and conduct comparative analysis of periglacial lagoons that are forming in various regions of Svalbard due to the climate change. This dataset can also be used to develop models of hydrological processes in periglacial water bodies of this nature, which arise from the interaction between a melting glacier and the influence of the sea.